PENGARUH PENAMBAHAN PAKAN BERBAHAN DASAR MAGGOT DAN DEDAK PADI PADA PAKAN BASAL TERHADAP BOBOT HIDUP, KARKAS DAN GIBLET AYAM BROILER - Kastalani Kastalani; Maria Erviana Kusuma; Herlinae Herlinae; Yemima Yemima (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The purpose of this study was to determine the effect of adding feed with maggot and rice bran as a base ingredient in basal feed on live weight, carcass and giblets of broiler chickens and to determine the rate of addition of feed with maggot and rice bran as a base ingredient in basal feed which will give good results. best on live weight, carcass and broiler chicken giblets. The implementation of this research took place at the practical location of the Faculty of Animal Husbandry, Palangka Raya Christian University, Jalan G.S Rubay Palangka Raya. This study used a completely randomized design (CRD) with 4 treatments with 5 replications, namely A = 100% basal feed, B = 100% basal feed and 5% additional feed, C = 100% basal feed and 10% additional feed and D = feed. basal 100% and additional feed 15%. From the results of the study, it can be seen that the addition of feed with maggot and rice bran as a base ingredient in basal feed has no effect on live weight, carcass and broiler chicken giblets.